Предмети середньовічного озброєння з Чорнівського городища першої половини ХІІІ ст. (дослідження 2012 р.) - Калініченко, Віталій; Пивоваров, Сергій (Львів, видавництво Львівської політехніки, 2014)
Проаналізовано предмети озброєння дальнього та ближнього бою, а саме наконечники стріл та бронзове навершя руків’я середньовічного меча, виявлені під час дослідження Чорнівського городища першої половини ХІІІ ст. у 2012 р. Здійснено типологізацію та аналіз предметів озброєння. Виявлені матеріали містять важливі дані з військово-політичної історії Буковини та дають змогу простежити взаємовідносини військового контингенту Чорнівського городища із суміжними територіями Русі та Європи у ХІІІ ст. This article analyzes of armaments and long-range melee, such as arrowheads and bronze pommel handle medieval sword found during research Chornivska hillfort first half of the XIII century in 2012. The authors typology and analysis of armaments. The authors introduced into scientific circulation quite rare for the region discovery, namely head bronze finial medieval sword hilt, which was discovered on the Chornivka hillfort first half of XIII century in 2012. Argued that the head pommel sword has baltic origin. Detection allows us to trace and find more to explore military affairs of the local population, in particular to trace mutual troop Chornivka hillfort with adjacent territories of Russia and Europe in the XIII century. The purpose of this study is to put into circulation actually first discovery details of the sword, which clearly can be attributed to XII – early XIII сеntury from Siret territory to the Middle Dniester river interfluve, namely head pommel or handle of a medieval sword and a comprehensive review of the findings, it’s analysis, interpretation and implementation types. Consequently, the typology A. Kirpichnikova by their morphological features head pommel sword with Chornivka hillfort of the type I – swords with bronze cross bronze pommel with five or seven parts. The shape of the pommel blades of this type are similar to swords such as K, S, and T1 by typologically V. Kazakyavichusa. Bronze swords of the given type, as indicated by A. Kirpichnikov with cast ornament with circles characteristic of romance art ХІІ century. This type of sword was the inscription on the blade. All findings of this type swords found in the settlements and burials of the XII-XIII century.
Keywords: наконечники стріл; навершя руків'я меча; Чорнівське городище; типологізація; Буковина